2012
DOI: 10.3389/fnhum.2012.00209
|View full text |Cite
|
Sign up to set email alerts
|

Near-death experiences between science and prejudice

Abstract: Science exists to refute dogmas; nevertheless, dogmas may be introduced when undemonstrated scientific axioms lead us to reject facts incompatible with them. Several studies have proposed psychobiological interpretations of near-death experiences (NDEs), claiming that NDEs are a mere byproduct of brain functions gone awry; however, relevant facts incompatible with the ruling physicalist and reductionist stance have been often neglected. The awkward transcendent look of NDEs has deep epistemological implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 68 publications
(90 reference statements)
0
41
2
1
Order By: Relevance
“…Use of these unique experimental paradigms will allow detailed mechanistic dissection of neurophysiology of the dying brain in animal models, which could provide guidance for research on NDE after cardiac arrest in humans. NDE represents a biological paradox that challenges our understanding of the brain and has been advocated as evidence for life after death and for a noncorporeal basis of human consciousness (39)(40)(41)(42), based on the unsupported belief that the brain cannot possibly be the source of highly vivid and lucid conscious experiences during clinical death (9,12). By presenting evidence of highly organized brain activity and neurophysiologic features consistent with conscious processing at near-death, we now provide a scientific framework to begin to explain the highly lucid and realer-than-real mental experiences reported by near-death survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of these unique experimental paradigms will allow detailed mechanistic dissection of neurophysiology of the dying brain in animal models, which could provide guidance for research on NDE after cardiac arrest in humans. NDE represents a biological paradox that challenges our understanding of the brain and has been advocated as evidence for life after death and for a noncorporeal basis of human consciousness (39)(40)(41)(42), based on the unsupported belief that the brain cannot possibly be the source of highly vivid and lucid conscious experiences during clinical death (9,12). By presenting evidence of highly organized brain activity and neurophysiologic features consistent with conscious processing at near-death, we now provide a scientific framework to begin to explain the highly lucid and realer-than-real mental experiences reported by near-death survivors.…”
Section: Discussionmentioning
confidence: 99%
“…These near-death experiences (NDE) (8), reported worldwide across cultures (9), are described to be highly lucid and vivid, and are perceived to be "realer than real" (10). Whether and how the brain is capable of generating conscious activity during cardiac arrest has been vigorously debated (11)(12)(13). We reasoned that if NDE stems from brain activity, neural correlates of consciousness should be identifiable in humans or animals after cessation of cerebral blood flow.…”
mentioning
confidence: 99%
“…In recent years several psychobiological interpretations have been proposed, but none of them has been proved so far, while some of them are contradicted by the available data (see (11), as a review). For instance, it was suggested that retinal ischemia might explain the tunnel-like vision (12).…”
Section: Scientific Interpretations Of Ndesmentioning
confidence: 98%
“…It seems that there are thousands, indeed millions, of people worldwide with stories to tell, communicating what they had of themselves seen, heard and felt, and thousands of credible death-and-return reports, as apparently there have been since the beginning of time. These returns are well attested from ancient times: from Plato himself, great philosopher and observer of antiquity, to the evidence of a hardnosed and previously strongly skeptic neurological surgeon, Eben Alexander (2012), supported by numerous others (Anon 2017a;Facco and Agrillo 2012;Van Lommel 2011;Worrall 2014 are only a few examples among the many scholarly-scientific not speculative-studies).…”
Section: Death and Communicatingmentioning
confidence: 97%